492 Pain and falls among persons with multiple sclerosis. - Libak Abou; Anna Kratz (Journal of Clinical and Translational Science, 2024)
OBJECTIVES/GOALS: Falls are very common among persons with multiple sclerosis (PwMS) due to the disabling symptoms associated with the disease. The relationship between pain and falls is underexplored. This study investigated the relationship between the facets of pain (intensity and interference) and falls in the context of co-occurring symptoms of MS. METHODS/STUDY POPULATION: This is a survey-based study that included 915 adults with MS. Participants provided data on demographics, clinical data, concerns about falling, symptom severity, and occurrence of falls in the past 6 months. Participants also completed the Patient Reported Outcome Measurement Information System (PROMIS) pain interference and pain intensity short forms. Pain interference and pain intensity were separately entered into univariate and multivariable logistic regression models developed to examine the associations between falls incidence and pain. Multivariable models were adjusted for age, sex, years since diagnosis, MS type, Patient Determined Disease Steps, MS status, concerns about falling, fatigue severity, PROMIS depression short form, and PROMIS physical function short form. RESULTS/ANTICIPATED RESULTS: Univariate regression analyses indicated that pain interference (OR = 1.05; 95% CI 1.03 to 1.06; p < 0.01) and pain intensity (OR = 1.03; 95% CI 1.02 to 1.04; p < 0.01) were both associated with falls. Only pain interference remained significantly associated with falls in multivariable regression analysis (OR = 1.02; 95% CI 1.00 to 1.05; p = 0.03). The model explained 25% of the variance in falls. Pain intensity was not associated with falls (OR = 0.98; 95% CI 0.95 to 1.01; p > 0.05) in multivariable regression analysis. DISCUSSION/SIGNIFICANCE: The findings suggest that pain is associated with falls among PwMS. Interventions designed to reduce falls incidence among PwMS may consider the inclusion of pain management as an integral component of those programs.